ENHANCING BANKING FUTURE PERFORMANCE: REVALUATION AND BOOK-TO-MARKET RATIO - Magdalena, Maria; Heriyadi, Heriyadi; Malini, Helma; Azazi, Anwar; Mustika, Uray Ndaru (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The banking sector played a crucial role in global economic stability, supporting financial and investment activities. Prior to making funding decisions within the banking sector, investors required reliable information disclosure. The assessment of book value and asset management were strategic steps that provided a precise representation of the company’s fundamental value, compared to volatile market value. This research aimed to investigate how the book-to-market ratio mediated the relationship between asset revaluation, return on assets, debt equity ratio, and future financial performance (ROE). Employing quantitative approach with multiple regression analysis using EViews 13. Path analysis was utilized to examine the mediation effect. This research conducted an unbalanced panel analysis consisting of 80 observations from 30 Indonesian banks listed on the Indonesia Stock Exchange from 2014 to 2022 that fulfilled the sampling criteria. Data is derived from annual financial reports and selected through purposive sampling criteria focused on the presence of asset revaluation. The finding of this research indicated that asset revaluation negatively affects the book-to-market ratio when ROA has a positive relationship. ROA and book-to-market ratio positively affect debt equity ratio. Then, ROA has a significant positive impact on banking future performance, while DER has a significant negative relationship. Conversely, the book-to-market ratio proven can mediate the relationship between asset revaluation and debt equity ratio